2002
DOI: 10.1128/iai.70.9.5081-5085.2002
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioside Mimicry ofCampylobacter jejuniLipopolysaccharides Determines Antiganglioside Specificity in Rabbits

Abstract: The core oligosaccharides of Campylobacter jejuni lipopolysaccharides (LPS) display molecular mimicry with gangliosides. Cross-reactive anti-LPS-antiganglioside antibodies have been implicated to show a crucial role in the pathogenesis of the Guillain-Barré and Miller Fisher syndrome. The specificity of the antiganglioside response is thought to depend on the oligosaccharide structure of the ganglioside mimic. To test this hypothesis and to investigate the potential of LPS from Campylobacter strains from enter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…41 The specificity of antiganglioside antibody induced by immunization of C jejuni LOS overall corresponds to ganglioside epitopes on the LOS in rabbits. 42 In this study, we showed that the target ganglioside (GM1, GD1a, or GQ1b) for serum autoantibody corresponds to the LOS-mimicking gangliosides of isolates from individual patients. However, other gangliosides such as GM1b and GalNAc-GD1a could be target antigens for autoantibodies in GBS 30 and further investigation is necessary to explain the variety of the clinical manifestation of GBS in more detail.…”
Section: Results Cst-ii Gene Frequency and Polymorphism (Thr/ Asn51mentioning
confidence: 99%
“…41 The specificity of antiganglioside antibody induced by immunization of C jejuni LOS overall corresponds to ganglioside epitopes on the LOS in rabbits. 42 In this study, we showed that the target ganglioside (GM1, GD1a, or GQ1b) for serum autoantibody corresponds to the LOS-mimicking gangliosides of isolates from individual patients. However, other gangliosides such as GM1b and GalNAc-GD1a could be target antigens for autoantibodies in GBS 30 and further investigation is necessary to explain the variety of the clinical manifestation of GBS in more detail.…”
Section: Results Cst-ii Gene Frequency and Polymorphism (Thr/ Asn51mentioning
confidence: 99%
“…These bacteria bear lipopolysaccharide (LPS) molecules that cross-react with gangliosides [73][74][75]. In these cases, the antibody specificities have been shown to correspond to the structure of the cross-reactive LPS oligosaccharides [76,77], and production of anti-ganglioside antibodies with the same specificities has been induced by immunization of animals with the LPS species [78]. In CD, a mouse monoclonal immunoglobulin (Ig) G antigliadin antibody has been shown to cross-react with human cerebellar tissue, possibly indicating its involvement in CD ataxia, although the target antigen has not yet been characterized [52].…”
Section: Anti-ganglioside Antibodies In Celiac Neuropathymentioning
confidence: 99%
“…First, a high dose ( colony-forming 9 1 ϫ 10 units [CFUs]) of C. jejuni has been required to achieve a у75% attack rate [10]. Second, the outer lipooligosaccharide (LOS) core of the 81-176 strain synthesizes ganglioside mimics, a mechanism by which C. jejuni infection is thought to induce GBS [11][12][13][14].…”
mentioning
confidence: 99%